The Toxicity Processes of Environmental Pollutants - Suwanaruang, Theeranat (The Toxicity Processes of Environmental Pollutants, 2023)
Toxic pollutions are noxious or poisonous contamination of the air, land, and water. It also includes sewage and particulates from power plants, as well as industrial wastes like dangerous heavy metals from mining or chemicals from companies. Toxic pollution is distinguished from pollution from higher carbon dioxide levels, which contributes to climate change but has no immediate negative effects on health. Drinking water, fish in rivers and ponds, food grown on contaminated fields, playgrounds, residences, and even the air we breathe can all be contaminated by toxic pollutants. Therefore, if you live in an area that is polluted, you might be exposed to these toxins whenever you eat, drink, wash, play, or breathe.